Adolescent daughters' perceptions of their fathers' levels of communication and care: How these variables influence female adolescent sexual behaviors. Issue 5 (4th July 2018) - Sentino, Patrice; Thompson, Phyllis L.; Nugent, William R.; Freeman, Derrick
ABSTRACT: This study examines the relationship between female adolescents' perceptions of their fathers' level of communication and care, and the influence of these variables on their adolescent daughters' sexual behaviors. Data was extracted from the National Longitudinal Study of Adolescent Health from 1994–2008, which consisted of a sample ( N =629) of adolescent girls in grades 7–12 in the United States during the 1994–1995 school year. Study results show fathers' caring as statistically significant at the .05 level. As fathers' caring increased, the number of sex partners decreased among adolescent girls. Fathers' communication was not statistically significant at the .055 level. However, as the daughters' perception of their fathers' communication improved, the number of daughters' sex partners decreased. The high rates of unintended pregnancy, unprotected sex, and sexually transmitted infections (STI's) among U.S. adolescent females show the need for a greater understanding of how fathers contribute to their daughters sexual risk-taking behaviors. Implications for practice and future research is discussed.